The influence of human factors and specialist involvement on information systems success. - Martinsons, Maris G.; Chong, Patrick K. C. (Human Relations, 1999)
Despite remarkable advances in information technology (IT), many computer-based information systems (IS) still fall short of performance expectations. A growing share of these implementation failures are due to nontechnical factors. This article considers the human factors and human resource (HR) management issues associated with IT assimilation. A taxonomy of specialist roles in the IS adoption process is proposed and illustrated in a series of brief case studies. The results from a field investigation are then reported. The relationships between different HR specialist roles and selected IS success measures were examined in more than 60 organizations across East and Southeast Asia. Proactive and supportive HR roles were found to be associated with greater user satisfaction, smoother organizational change and improved productivity, but did not significantly affect perceived output quality. The implications for management practice are discussed and specific areas for further research are identified. Reprinted by permission of the publisher.